2010
DOI: 10.1149/1.3497353
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Ionic Wirings Versus the Insertion Reaction Contributions to the Polarization in LiFePO[sub 4] Composite Electrodes

Abstract: The different contributions to the polarization of a LiFePO 4 electrode are experimentally discriminated in this work. The electrode total resistance is dominated at high rate by the contribution of the electronic and the ionic wires, the former being more important in the case of electrodes with low compaction, while the latter being more important in the case of electrodes with high compaction. A porosity in the 35%-40% range allows to minimize the electrode polarization. At low rate, the electrode resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 46 publications
4
63
1
Order By: Relevance
“…This result differs from the literature that sparse LiFePO 4 -based composite electrodes are suffer from capacity decrease due to the electronic transportation limitations [18], which can be ascribed relatively poor electronic conductivity of the active material LiFePO 4 as compared with NCM. When the electrode density is further increased to 3.36 g cm À3 , the specific capacity decreases and finally yields the specific capacity of 70 mAh g À1 at the minimum.…”
Section: Packing-limitation Of Active Materials In the Composite Eleccontrasting
confidence: 97%
“…This result differs from the literature that sparse LiFePO 4 -based composite electrodes are suffer from capacity decrease due to the electronic transportation limitations [18], which can be ascribed relatively poor electronic conductivity of the active material LiFePO 4 as compared with NCM. When the electrode density is further increased to 3.36 g cm À3 , the specific capacity decreases and finally yields the specific capacity of 70 mAh g À1 at the minimum.…”
Section: Packing-limitation Of Active Materials In the Composite Eleccontrasting
confidence: 97%
“…Typically, the ionic and electronic conductivity strongly depend on the porosity of the electrode matrix having an optimum around 35% porosity [ 25 ] which is typically aimed for in electrode preparation. Given the current results it is interesting to fi nd how nucleation, electronic, and ionic conduction play a role at variable cycling rates in other two phase materials.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of LFP-based electrode we briefly commented on this feature some time ago and termed it an "activation" phenomenon. 48 Later on, Lestriez et al 43 performed a more systematic analysis of the measured galvanostatic curves of LFP electrodes and confirmed the existence of the phenomenon. They have also observed a similar non-linear characteristic for the case of nano-sized Si-based negative electrode.…”
Section: Total Resistance Of the Cell R Total And The "Activation"mentioning
confidence: 91%
“…Namely, it is well known that the measured electrochemical performance of Li ion insertion electrodes is strongly affected by the electrode morphology (electrode thickness, porosity and packing density) which has impact on the course of overpotential curve and, consequently, on the obtained capacity. For the case of LFP based electrodes, this impact was systematically and thoroughly addressed by Lestriez et al 43,44 and later effectively demonstrated in a major practical high-rate improvement of Li 4 Ti 5 O 12 45 and of LFP 46 based electrodes. In the present specific case the effect of different wiring contribution could manifest itself through the higher density (approx.…”
Section: Current-overpotential (I-η η) Characteristicsmentioning
confidence: 99%